2023
DOI: 10.1002/wer.10821
|View full text |Cite
|
Sign up to set email alerts
|

Clogging index: A tool to quantify filter bed clogging in horizontal subsurface flow macrophyte‐assisted vermifilter

Abstract: This study aimed to develop a mathematical index for quantifying filter bed clogging in horizontal subsurface flow macrophyte-assisted vermifilter (HSSF-MAVF). The developed clogging index (CI) simulates the porosity reduction in the HSSF-MAVF bed due to the combined actions of deposition of suspended solids, biofilm generation, and plant growth. A series of experiments based on HSSF-MAVF were conducted to examine the key parameters related to clogging of the vermifilter such as hydraulic loading rates (HLR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…According to Suhaib and Bhunia [ 65 ], the instability of earthworm casts within the filter bed at higher HLRs can further reduce the beds’ permeability. Moreover, the studies conducted by the same authors [ 66 ] revealed that a filter bed at an HLR of 2.34 m 3 /m 2 /day causes an increase in organic and suspended solid loads on the filter bed compared to a (lower) HLR of 0.66 m 3 /m 2 /day, resulting in significant accumulation of clogging materials like biofilm biomass and suspended solids at the inlet end of the filter bed.…”
Section: Different Factors To Consider In the Implementation Of A Ver...mentioning
confidence: 99%
“…According to Suhaib and Bhunia [ 65 ], the instability of earthworm casts within the filter bed at higher HLRs can further reduce the beds’ permeability. Moreover, the studies conducted by the same authors [ 66 ] revealed that a filter bed at an HLR of 2.34 m 3 /m 2 /day causes an increase in organic and suspended solid loads on the filter bed compared to a (lower) HLR of 0.66 m 3 /m 2 /day, resulting in significant accumulation of clogging materials like biofilm biomass and suspended solids at the inlet end of the filter bed.…”
Section: Different Factors To Consider In the Implementation Of A Ver...mentioning
confidence: 99%